Consideraciones sobre las teorías de medición: un ejemplo de aplicación bajo la teoría de respuesta al ítem (TRI) (2001)
This article shows a review of the theories developed about the measurement of variables in psychology. It presents a historic revision and the main aspects of the Test Classic Theory (TCT), the Generalization Theory (GT) and the Item Response Theory (TRI).Given the importance that today has the TRI, a hipothetic example is used in order to explain and interpret some of the most important results of the information analyses supported by this theory.